Detection of bacterial species causing urinary tract infections in various parts of Libya's Brega city region, isolation, identification, and antibiotic sensitivity testing. - Sead. Najem, Mifthah; Fathi. Alsdig , Suliman.; F.Lawgali, Youssef. (Scientific Journal for Faculty of Science-Sirte University, 2023)
The purpose of the study is to ascertain the prevalence of Gram-positive and Gram-negative bacteria that cause urinary tract infections in patients in Brega of various Libyan ages. Inpatients and outpatients at Brega Qarawi Hospital (third zone), Family Clinic (first zone), and Industrialized Clinic (first zone) provided 500 mid-stream urine (MSU) specimens. These people ranged in age from 15 to 65 and included 285 men and 215 women. According to this study, UTI was 45% common in Brega City, with males having a higher frequency than females (46% vs. 44%). Adults (72.4%) were the age group most likely to have UTIs, followed by the elderly (16.4%) and teenagers (11.1%). The majority of those with UTI were outpatients (62.2%) and inpatients (37.7%). With 49.7% of infections caused by it, Escherichia coli was the most prevalent uropathogen. Pseudomonas aerogenosa and Klebsiella pneumoniae were each in charge of 10.2% and 20.8% of the cases, respectively. UTIs were less commonly caused by the gram-positive bacteria Staphylococcus aureus (5.3%) and Staphylococcus saprophylticus (2.6%). With the highest sensitivity of the antibiotics examined in this study, Imipenem is the one to use.